Analisis Potensi Wilayah Penyebab Banjir DAS Opak Dengan Memanfaatkan Penginderaan Jauh dan Sistem Informasi Geografis - Mawasta, Hanung, Dra. Alif Noor Anna, M.Si, Agus Anggoro Sigit, S. Si, M. Sc (2015)
Floods often occur in several rivers in the Opak Watershed. The impact that the various public facilities submerged, disrupting the activity of local communities and floods cause losses both social and economic. This study aims to 1) determine the magnitude of the peak discharge (Qp) Opak watershed using rational methods, 2) Knowing Opak sub watershed potentially cause flooding, 3) to analyze the biophysical parameters that influence the differences in water discharge in the Opak sub watershed. This research method using field survey method, combined Landsat imagery interpretation techniques, and using methods Cook and Rational method for calculating the maximum discharge of the formula Q max = CIA/360 m3/sec. Landsat 8 is done interpretation and processed into maps of land use, subsequently amended as vector data. Map RBI processed and obtained a high point, from a high point extracted into the map slope. Geographic Information Systems applied to overlay, fourth vector data (land use, soil texture, density flow and slope) to obtain price runoff coefficient (C). Using Gumbel distribution and formula Mononobe, rainfall data of 30 rainfall monitoring stations for 10 years (2005-2014) in the Opak Watershed processed to obtain maximum intensity value (I). The study area was divided into 10 sub watershed which is Winongo Kecil sub watershed, Winongo sub watershed, Bulus sub watershed, Mruwe sub watershed, Kuning sub watershed, Code sub watershed, Gajah Wong sub watershed, Wareng sub watershed, Opak Kecil sub watershed and Tepus sub watershed. The results showed sub watershed which that have potential flood there are 4, namely, Code sub watershed with excess flow of 17,72 m3/ sec, due to have a run off coefficient which is great on landuse, Kuning sub watershed is 15,53 m3/sec, due to having a large coefficient of run off on slope, Winongo Kecil sub watershed is 23,34 m3/sec, due to have a run off coefficient which is great on landuse and Bulus sub watershed is 16,97 m3/sec due to having a large coefficient of run off on the soil texture.Soil texture in Bulus sub watershed is clay, the texture has nature hard to absorb water, so when the rains come this area will be inundated and the resulting value becomes large run off. Keywords: Remote Sensing and Geographic Information Sisitem, Gumbel distribution, Maximum discharge, Rational Method, Formula Mononobe.